The semiquinone radical anion of 1, 10-phenanthroline-5, 6-dione: synthesis and rare earth coordination chemistry. Issue 80 (21st September 2018) - Hickson, James R.; Horsewill, Samuel J.; McGuire, Jake; Wilson, Claire; Sproules, Stephen; Farnaby, Joy H.
Abstract : The redox-active ligand as a route to heterobimetallic rare earth-transition metal compounds containing a semiquinone radical anion. Abstract : Reduction of 1, 10-phenanthroline-5, 6-dione (pd) with CoCp R 2 resulted in the first molecular compounds of the pd˙ − semi-quinone radical anion, [CoCp R 2 ] + [pd]˙ − (R = H, (1 ); R = Me4, (2 )). Furthermore compounds1 and2 were reacted with [Y(hfac)3 (thf)2 ] (hfac = 1, 1, 1-5, 5, 5-hexafluoroacetylacetonate) to synthesise the rare earth-transition metal heterometallic compounds, [CoCp R 2 ] + [Y(hfac)3 ( N, N ′-pd)]˙ − (R = H, (3 ); R = Me4, (4 )).